(3QSGdI JbdjO SajQ GdbOQIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3GdMeO dehdGfG hMOg dGTQjc dg ai GdSQGA hGdVQGA hGdTOI hGdQNGA ef YHO ehdGfG heedhcg bGFe GdReGf Edi GdTjN SajQ GdbOQI aNQ GdehMOjf s
(3BNQgG (B:s
(3hJhUd LhGHGJgG hJfaP Edi hdOi Ydi hMSjf GdeCPhfjf ai GdOYhI CjOgeG Gdehdi HhUhdgeG Edi GdLGQjI Je GdJbdjO hGdMeO dehdGfG hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B22s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJhMjO hGdedd hGdfMds